Study of an energy regeneration system with accumulator for hydraulic impulse testing equipment - Man, Zaipeng (Strojniški vestnik, 2015)
To guarantee the reliability and performance of hydraulic systems, it is of vital importance to do hydraulic impulse testing for hydraulic components. However, the testing time is usually so long that the energy consumption is very large. An energy regeneration system with an accumulator is proposed and used for hydraulic impulse testing equipment. Mathematical analysis and simulations show that the hydraulic impulse testing system with an accumulator can reduce energy consumption by 15% compared with that of the system without an accumulator in the cycle. Furthermore, the energy efficiency of the hydraulic impulse testing system is increased from 62.82 to 75.71% by the use of an accumulator. Both simulation results and experimental results show that the control performance of the hydraulic impulse testing equipment with an accumulator is better than that of the equipment without an accumulator, and has a faster response speed and a larger pressure rise rate.
Keywords: eksperimenti; hidravlični akumulatorji; preizkušanje hidravličnih impulzov; regeneracija energije; shranjevanje energije; simulacije